PROTECTIVE EFFECT OF PURPLE SWEET POTATO (Ipomoea batatas L.) EXTRACT ON GENTAMYCIN-INDUCED WISTAR RATS LIVER CELLS - Anggraeny, Dian; Noneng Nawangsih, Eka; Falah Arrafi, Moch (Fakultas Kedokteran Gigi Unjani, 2025)
Gentamicin is a commonly used antibiotic for treating aerobic gram-negative bacterial infections. However, it has hepatotoxic effects that can damage liver hepatocyte cells through the generation of free radicals. Antioxidant compounds are needed to neutralize these free radicals and prevent cellular damage. Purple sweet potato (Ipomoea batatas L.) is known to be rich in anthocyanins, which possess antioxidant properties. This study aimed to determine the effect of ethanol extract of purple sweet potato (Ipomoea batatas L.) on liver histopathology in Wistar rats exposed to gentamicin. This was a laboratory experimental study using 24 male Wistar rats divided into four groups (n=6 per group). Group K1 served as a negative control. Group K2 was a positive control, induced with gentamicin 80 mg/kgBW/day subcutaneously for 8 days. Group P1 received 200 mg/head of purple sweet potato ethanol extract orally along with gentamicin for 8 days. Group P2 received 400 mg/head of the extract orally along with gentamicin for 8 days. Liver damage was assessed using histopathological examination and scored based on the Manja Roenigk criteria. Data were analyzed using one-way ANOVA followed by Tukey’s post hoc (p<0.05). Results are the highest degree of hepatocyte damage was observed in Group K2. Group P1 showed a significant reduction in liver cell damage compared to Group K2 (p<0.05), indicating hepatoprotective activity at a dose of 200 mg/head. In contrast, Group P2 showed a higher damage score than Group P1, suggesting reduced effectiveness at the higher dose. Conclusion is ethanol extract of purple sweet potato at a dose of 200 mg/head demonstrated better hepatoprotective effects compared to a dose of 400 mg/head in Wistar rats exposed to gentamicin. DOI : 10.54052/jhds.v5n1.p89-100